PENGEMBANGAN MODUL AJAR BERBASIS HOTS PADA MATERI RIAS CIKATRI KELAS XI SMK NEGERI 2 JOMBANG - Elvi Putri Gunawan; Nia Kusstianti; Sri Usodoningtyas; Dindy Sinta Megasari (Program Studi Pendidikan Tata Rias, 2024)
The development of this HOTS-based teaching module is the development of a teaching module which aims to help students get used to thinking critically and creatively in learning activities with the help of HOTS (high level thinking) which is applied in the teaching module to help students get used to thinking critically and creatively in learning activities . Finding out how HOTS-based teaching modules were developed at SMKN 2 Jombang, their viability, student learning results, and student reactions to utilizing them with cikatri makeup material are the goals of the study. R&D (Research and Development) is the sort of research that is used. Overall media feasibility may be classified as